2017
DOI: 10.1016/j.cpr.2017.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of group social skills interventions for youth with autism spectrum disorder: A systematic review and meta-analysis

Abstract: Group-based social skills interventions (GSSIs) are widely used for treating social competence among youth with autism spectrum disorder (ASD), but their efficacy is unclear. Previous meta-analysis of the literature on well-designed trials of GSSIs is limited in size and scope, collapsing across highly heterogeneous sources (parents; youths; teachers; observers; behavioral tasks). The current meta-analysis of randomized control trials (RCTs) was conducted to ascertain overall effectiveness of GSSIs and differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
256
3
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 304 publications
(273 citation statements)
references
References 110 publications
(156 reference statements)
13
256
3
1
Order By: Relevance
“…However, concerns have been raised about the generalizability of social skills training in a clinical setting to daily functioning in the community. Increased focus on practicing social skills in various contexts and community settings (“programming for generalization”) may maximize the impact of social skills training on real-world functioning (Gates, Kang, & Lerner, 2017). …”
Section: Discussionmentioning
confidence: 99%
“…However, concerns have been raised about the generalizability of social skills training in a clinical setting to daily functioning in the community. Increased focus on practicing social skills in various contexts and community settings (“programming for generalization”) may maximize the impact of social skills training on real-world functioning (Gates, Kang, & Lerner, 2017). …”
Section: Discussionmentioning
confidence: 99%
“…In schizophrenia, poor social cognitive ability predicts social skills and daily living skill ability, suggesting social cognition is an important area to target in treatments [Pinkham, Harvey, & Penn, ]. Social cognitive challenges may also relate to difficulties with social functioning for adults with ASD [Sasson et al, ], but training programs developed to target social cognition in ASD have shown inconsistent effects [Bishop‐Fitzpatrick, Minshew, & Eack, ] and often result in only modest improvements that do not generalize well to real‐world functioning [Gates, Kang, & Lerner, ]. The inconsistency and limited efficacy of these programs may occur in part because of the variable ways social cognition is operationalized and measured across treatment and research studies with ASD adults [Kliemann & Adolphs, ].…”
Section: Introductionmentioning
confidence: 99%
“…Because autistic adults without intellectual disability often perform poorly on measures of social cognition [Morrison et al, 2019;Velikonja, Fett, & Velthorst, 2019], including in the areas of social attention [Pelphrey et al, 2002;Sasson et al, 2007], affect recognition [Eack, Mazefsky, & Minshew, 2015], and advanced theory of mind [Baron-Cohen, Jolliffe, Mortimore, & Robertson, 1997], programs often focus on social cognition and explicitly teach strategies for improving performance Kandalaft, Didehbani, Krawczyk, Allen, & Chapman, 2013;Koegel, Ashbaugh, Navab, & Koegel, 2016;Turner-Brown, Perry, Dichter, Bodfish, & Penn, 2008]. Indeed, these programs often do improve performance on specific tasks [Bishop-Fitzpatrick, Minshew, & Eack, 2014;Kandalaft et al, 2013;Koegel et al, 2016], and confer other benefits like increasing knowledge about social skills [Gates, Kang, & Lerner, 2017] and facilitating friendship development when a peer group component is included [Spain & Blainey, 2015]. Unfortunately, such success has largely not generalized to broader real-world improvement in social and functional outcomes [Bottema-Beutel, Park, & Kim, 2018;Gates et al, 2017].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, these programs often do improve performance on specific tasks [Bishop-Fitzpatrick, Minshew, & Eack, 2014;Kandalaft et al, 2013;Koegel et al, 2016], and confer other benefits like increasing knowledge about social skills [Gates, Kang, & Lerner, 2017] and facilitating friendship development when a peer group component is included [Spain & Blainey, 2015]. Unfortunately, such success has largely not generalized to broader real-world improvement in social and functional outcomes [Bottema-Beutel, Park, & Kim, 2018;Gates et al, 2017].…”
Section: Introductionmentioning
confidence: 99%